2019
DOI: 10.1111/rec.12966
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation and herbivory during restoration of California coastal sage scrub

Abstract: Using nurse plants to facilitate native plant recruitment in degraded habitats is a common restoration practice across various arid and semiarid environments. Living trees or shrubs are typically considered nurse plants, whereas dead shrubs left in the landscape from prolonged drought are understudied prospective facilitators for native plant recruitment. The interaction between nurse plants and biotic pressures, such as herbivory, on native recruitment is also not well understood in semiarid plant communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…At the beginning of the experiment, we were unsure how herbivores would impact A. californica seedling recruitment and survivorship, and thus CSS recovery. While recent research has shown that herbivores reduce shrub seeding survivorship in intact CSS [39,40], we were unsure if similar patterns would be found in burned habitats. In particular, we wanted to explore the relative importance of competition with non-native annual grasses, which are often consumed by the herbivore community, as opposed to the direct effects of herbivores in limiting A. californica recruitment [15,59,60].…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…At the beginning of the experiment, we were unsure how herbivores would impact A. californica seedling recruitment and survivorship, and thus CSS recovery. While recent research has shown that herbivores reduce shrub seeding survivorship in intact CSS [39,40], we were unsure if similar patterns would be found in burned habitats. In particular, we wanted to explore the relative importance of competition with non-native annual grasses, which are often consumed by the herbivore community, as opposed to the direct effects of herbivores in limiting A. californica recruitment [15,59,60].…”
Section: Discussionmentioning
confidence: 83%
“…Similar actions are not be required for native forbs, except near the fire edge where caging may be critical for CSS recovery. For example, we recommend that restoration studies explore the efficacy of caging individual seedlings [39,40] or larger areas like we did here, and potentially targeting non-native grass removal efforts in these treatments [15], as this could increase shrub survivorship and enhance the likelihood of CSS recovery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vertebrate herbivore communities in coastal sage scrub ecosystems are diverse, consisting of squirrels ( Sciurus niger and Otospermophilus beecheyi ), rabbits ( Sylvilagus audubonii ), and woodrats and mice ( Nassella lepida , Nyctinomops macrotis , Peromyscus eremicus , and Cantharellus californicus ) (Quon et al, 2019 ). Some prefer young grasses or forbs over fresh shoots of A. californica during the growing season, but shift their feeding onto shrubs during the summer and fall when shrubs are particularly vulnerable (Genin & Badan‐Dangon, 1991 ; Genin & Pijoan, 1993 ).…”
Section: Methodsmentioning
confidence: 99%